Training On Business Ethics And Basic Bookkeeping For MSME Actors In Kampung Cincau, Gudang Subdistrict - Syarif, Rini; Sutomo, Hadi; Soedargo, Bayu Prasetyo; Imelda, Imelda; Raya, Ramadhan (Jurnal Abdimas Dedikasi Kesatuan, 2025)
The development of micro, small, and medium enterprises (MSMEs) requires a solid foundation in both ethical business conduct and basic financial recording skills. In Kampung Cincau, Kelurahan Gudang, many MSME actors still lack sufficient understanding of business ethics principles and do not possess basic bookkeeping skills. This community service activity aims to provide training on business ethics and basic bookkeeping to enhance MSME performance and credibility. The methods used include interactive seminars, ethical case simulations, and bookkeeping workshops based on daily business transactions. The results showed that 78% of participants were able to understand business ethics values and independently prepare basic financial reports. This activity is a strategic step in strengthening MSME capacity through ethical and financial literacy.